Going the Distance - Online Course Performance and Motivation of Distance-Learning Students - Hobson, Tiffaney D; Puruhito, Krista Kay (Online Learning, 2019)
This study was designed to better understand what drives the learning and performance of students enrolled in distance-learning courses. Between 1999 and 2008, the number of students enrolled in at least one online course increased from 10% to 24% (NCES, 2014). In 2015, the number of students enrolled in at least one distance-learning course approached 6 million, with close to half of those students enrolled in programs that are exclusively online (NCES, 2018; Allen & Seaman, 2017). This enrollment growth, however, is coupled with an alarmingly high attrition rate - a rate as high as 50% greater than campus-offered programs (Willging & Johnson, 2009). As GPA and course performance have been linked to distance-learning persistence and retention, we found it imperative to explore differences in motivational orientations as they relate to passing and failing status for an individual course. To do so, we surveyed distance learning students and identified correlations between motivational constructs such as instrumentality, self-efficacy, connectedness, use of knowledge building strategies, and final course performance. Differences related to gender and major/non-major status are also reviewed and discussed. These findings offer insights into next steps for research, but also inform teaching practice.